1999
DOI: 10.1002/(sici)1096-9071(199905)58:1<79::aid-jmv13>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Identification of JC virus variants in multiple tissues of pediatric and adult PML patients

Abstract: The transcriptional control region (TCR) of JC virus (JCV), the causative agent of progressive multifocal leukoencephalopathy (PML), undergoes rearrangement during replication of the virus in its human host. The mechanism by which viral promoter/enhancer sequences are deleted and duplicated within the TCR of the archetype form of JCV is not understood, but it is hypothesized that the generation of JCV variants with rearranged TCRs contributes to the virus's pathogenic potential. In a recent study of a pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In the present study, an important finding is that PCR-detected JCV DNA in urine represents an infectious form of the virus, since JCV DNA was detected in COS-7 cells inoculated with urine samples from healthy volunteers. Urinary JCV contained archetypal regulatory regions, a finding that is consistent with the notion that the transmitted form of the virus has this arrangement [28,44,45]. Furthermore, within a given individual, the JCV sequences that were analyzed in multiple samplings over the course of this study remained stable.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, an important finding is that PCR-detected JCV DNA in urine represents an infectious form of the virus, since JCV DNA was detected in COS-7 cells inoculated with urine samples from healthy volunteers. Urinary JCV contained archetypal regulatory regions, a finding that is consistent with the notion that the transmitted form of the virus has this arrangement [28,44,45]. Furthermore, within a given individual, the JCV sequences that were analyzed in multiple samplings over the course of this study remained stable.…”
Section: Discussionsupporting
confidence: 82%
“…PCR analyses have demonstrated that JCV may persist in the brain, tonsils and lymphocytes of individuals with and without PML [2, 6-11, 13, 16, 40, 41] and it was proposed that JCV might employ B-lymphocytes to cross the BBB [8, 12, 14-16], similar to HIV and simian immunodeficiency virus (SIV), which gain entry into the brain via infected monocytes (Trojan horse) [42]. Further studies also suggested presence of JCV DNA in the PBMC of 17.4% of 69 HIV-1-positive immunocompetent patients, in 23.2% of 82 HIV-1-positive immunocompromised patients, and in 60% of AIDS patients with PML [43].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, endothelial cells have been shown to support BKV replication in vitro , raising the possibility that BKV may cross the endothelial barrier to disseminate from the periphery to its target organs via blood (Hanssen Rinaldo et al, 2005). There are rare reports of JCV sequence detection in various tissues and cells including the liver, lung, spleen, lymph nodes, and colorectal epithelium (Caldarelli-Stefano et al, 1999; Doerries, 2001; Grinnell et al, 1983; Laghi et al, 1999; Newman and Frisque, 1997; Newman and Frisque, 1999). While JCV reactivation leads primarily to infection of the brain, it is unclear whether normal brain tissue harbors the virus (Doerries, 2001).…”
Section: General Aspects Of Polyomavirus Infectionmentioning
confidence: 99%